NARRATIVE, PERCEPTION, AND THE EMBODIED MIND towards a neuro-narratology. - Farmasi, Lilla ([S.l.] : ROUTLEDGE, 2022)
This book encourages cross-disciplinary dialogues toward introducing a new framework for neuro-narratology, expanding on established theory within cognitive narratology to more fully encompass the different faculties involved in the reading process. Toinvestigate narrative cognition, the book traces the ways in which cognitive patterns of embodiment - and the neural connections that comprise them - in the reading process are translated into patterns in narrative fiction. Drawing theories of episodic memories and nonvisual perception of space, Farmasi draws on theories of episodic memories and nonvisual perception of space in analyzing a range of narratives fromtwentieth century prose. The first set of analyses shines a light on perception and emotion in narrative discourses and the construction of storyworlds, while the second foregrounds the reader's experience. The volume makes the case for the fact that narratives need to be understood as dynamic elements of the interaction between mind, body, and environment, generating new insights and inspiring further research. This book will appeal to scholars interested in narrative theory, literary studies, cognitive science, neuroscience, and philosophy.
Keywords: LANGUAGE ARTS & DISCIPLINES / General; LANGUAGE ARTS & DISCIPLINES / Linguistics; Perception in literature; Emotions in literature; Discourse analysis, Narrative; Cognitive grammar; Psychology and literature